Rhetorical Structure on Writing Result and Discussion Section of Undergraduate Student’s Thesis at Muhammadiyah University of Bengkulu - Epi Wadison; Febby Indriani Robert (UNIVED Press, 2022)
AbstractThe objective of this research is to find out anddescribe the lack of the rhetorical structure used byEnglish Students in writing the result & discussionsection in the Thesis academic year 2020 period 1. Thisstudy use qualitative research, and used descriptivequalitative. The result of this research, the englishstudents still lack in write there are: in backgroundinformation and summarising result. And thediscussion of this research the english students stilllack in write: interpreting result, comparing result, andecaluating result. This reserach suggested the studentscan used rhetorical structure based on Yang & Allison(2003) model to write of research results anddiscussion section. The reason are: First, this model isbetter than theses guidebook of FKIP. Second, thismodel contains: background information, reportingresult, summarising result. Third, this model in writingdiscussion of the research contains: interpreting result,comparing result, accounting result and evaluatingresult.Keyword: Rhetorical Structure, Result and Discussion,Thesis